Social support Improved the quality of life among Covid-19 Survivors in Sumbawa - Kesuma, Evi Gustia; Purwadi, Hendri; Putra, Dewa Gede Sanjaya; Pranata, Satriya (Alta Dharma Publisher, 2022)
Introduction: Covid-19 infected has an impact on quality of life among patients. Objectives: The study aimed to analyze factors related to quality of life among Covid-19 survivors in Sumbawa. Moreover, identifying the most variable related to quality of life was the secondary aims of this study. Methods: A quantitative study with a cross-sectional survey approach was applied to COVID-19 survivors in the Sumbawa Regency, West Nusa Tenggara. One hundred one respondents were selected by using proportional random sampling technique. Two statistically analysis used such as chi-square test and multiple logistic regression. Results: The results showed that gender, age, occupation, education level and social support associated with quality of life among covid-19 survivors. Social support was highest factor to improve the quality of life. Recommendation: The role of families, communities, and the government becomes an important point to ensure that COVID-19 survivors get social support, particularly when 1 to 6 months of recovery